Gregório Bezerra na “Segunda trincheira”: história de militância política e resistências ao golpe e ditadura civil-militar no Estado de Pernambuco (1964-1983). - Barros, Euclebson Cruz de (2022)
This report aims to analyze part of the political trajectory of Gregório Lourenço Bezerra, also known as “man made of iron and flower”, for his firmness of purpose as a militant of the Brazilian Communist Party (PCB) and for his feeling of fraternity with the less wealthy. Gregório's combative position is highlighted here in a clipping from 1964 to 1983, which comprises the second coup d'état and subsequent civil-military dictatorship which he witnessed until his death. It is important to highlight that we will mention other historical moments lived by the same when we find the mentions can facilitate the reader's understanding. In our research, we established contacts with primary sources such as newspaper and magazine articles, documents such as processes and certificates, and the biography written by Gregório himself. For the analysis of these sources, we use historical theorists such as Michel de Certeau, François Dosse, Jacques Le Goff and Paul Ricoeur, to support us, respectively, in the exercise of historiographical narrative, the biographical field and issues involving history and memory, not to mention that texts complementary memorials were also important for the deepening of the theme. As a final product, we will present an illustrated digital booklet in pdf and flipbook formats, intended preferably for undergraduate students in History but which can serve a wider audience.